Characterization of quaternary chalcogenide As-Ge-Te-Si thin films - Amer, H.H.; Elkordy, M.; Zien, M.; Dahshan, A.; Elshamy, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Investigated in this paper is the effect of replacement of Te by Si on the optical
gap and some other physical operation parameters of quaternary chalcogenide As₃₀Ge₁₀Te₆₀₋xSix (where x = 0, 5, 10, 12 and 20 at.%) thin films. Thin films with the
thickness 100-200 nm of As₃₀Ge₁₀Te₆₀₋xSix were prepared using thermal evaporation
of bulk samples. Increasing Si content was found to affect the average heat of
atomization, average coordination number, number of constraints and cohesive energy of
the As₃₀Ge₁₀Te₆₀₋xSix alloys. Optical absorption is due to allowed non-direct transition,
and the energy gap increases with increasing Si content. The chemical bond approach has
been applied successfully to interpret the increase in the optical gap with increasing
silicon content.